2015
DOI: 10.4172/2167-0587.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ionospheric precursors related to an earthquake (M=7.8) of 16 April, 2013 using GPS-TEC measurements: Case study

Abstract: In the present paper, we analyze the GPS-TEC data observed at Agra station, India (27.2o N, 78o E) and also see the diurnal variations of global ionospheric maps (GIMs) TEC data over the epicenter of this earthquake (M=7.8) in Pakistan region for the month of April, 2013. We use a statistical technique for the analysis of data and identify the significant precursors using 3σ criterion. These precursors are found in form of enhancements on different days in the interval of 5-7 days prior to the earthquake. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Ionospheric anomaly as one of the earthquake precursors was first reported by Antselevich [1971]. Many lithosphere-atmosphere-ionosphere coupling mechanisms have been formulated since then, which include radon radioactivity and leakage of CH 4 , CO 2 , He, and H 2 carrier gases [Pulinets et al, 2000[Pulinets et al, , 2002Pulinets, 2004;Pulinets and Ouzounov, 2011] which ionize the near-ground atmosphere [Sorokin and Hayakawa, 2013], generating an anomalous vertical electric field [Tsolis and Xenos, 2010;Singh et al, 2012;Pundhir et al, 2015] which perturbs the ionosphere [Pulinets and Davidenko, 2014]. Other mechanisms include generation of acoustic pressure waves [Yuen et al, 1969;Astafyeva et al, 2013], release of positive holes [Freund, 2013], and underground emission of aerosols [Pulinets et al, 2000] emitting electromagnetic radiation, which can change the ionospheric electron density distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionospheric anomaly as one of the earthquake precursors was first reported by Antselevich [1971]. Many lithosphere-atmosphere-ionosphere coupling mechanisms have been formulated since then, which include radon radioactivity and leakage of CH 4 , CO 2 , He, and H 2 carrier gases [Pulinets et al, 2000[Pulinets et al, , 2002Pulinets, 2004;Pulinets and Ouzounov, 2011] which ionize the near-ground atmosphere [Sorokin and Hayakawa, 2013], generating an anomalous vertical electric field [Tsolis and Xenos, 2010;Singh et al, 2012;Pundhir et al, 2015] which perturbs the ionosphere [Pulinets and Davidenko, 2014]. Other mechanisms include generation of acoustic pressure waves [Yuen et al, 1969;Astafyeva et al, 2013], release of positive holes [Freund, 2013], and underground emission of aerosols [Pulinets et al, 2000] emitting electromagnetic radiation, which can change the ionospheric electron density distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Ouzounov et al [2015] investigated (Global Ionosphere Maps) GIM-GPS/TEC maps for M7.8 and M7.3 April 2015 devastating Nepal earthquakes to indicate close correlation between ionospheric anomalies and these events. Pundhir et al [2015] studied the April 2013 M7.8 Pakistan earthquake to show GPS TEC data anomaly at Agra, 5-7 days prior to it. Shah and Jin [2015], by examining global M ≥ 5 earthquake events during 1998-2014 using TEC from GIMs, showed that ionospheric anomaly occurs for events having M ≥ 6 and focal depth less than 60 km.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide efforts on the search of earthquake's precursors many past studies have analyzed ionospheric anomalies before the occurrence of seismic events. Some of these studies (e.g., Zakharenkova et al, 2006;Zakharenkova et al, 2008;Mubarak et al, 2009;Zhu et al, 2010;Zou and Zhao, 2010;Yao et al, 2012;Zhu et al, 2013;Xinzhi et al, 2014;Guo et al, 2015;Li et al, 2015;Pundhir et al, 2015;Alcay, 2016;Sharma et al, 2017;Akhoondzadeh et al, 2018;Sotomayor-Beltran, 2019) have confirmed the presence of ionospheric variations days before the occurrence of an earthquake. On the other hand, only a few studies (e.g., Zou, 2010;Xinzhi et al, 2014) have reported ionospheric anomalies a few days after an earthquake.…”
Section: Introductionmentioning
confidence: 90%
“…The search for earthquake precursors in the ionosphere is a very active field of research (e.g. Liu et al, 2004;Zakharenkova et al, 2006Zakharenkova et al, , 2008Zhao et al, 2008;Mubarak et al, 2009;Zhu et al, 2010;Zou and Zhao, 2010;Yao et al, 2012;Zhu et al, 2013;Wang et al, 2014;Xinzhi et al, 2014;Li et al, 2015;Guo et al, 2015;Pundhir et al, 2015;Alcay, 2016). There are studies that for example concentrate on a particular earthquake and through the employment of different techniques, they are able to identify ionospheric anomalies that appear a few days before and which are associated to an earthquake.…”
Section: Introductionmentioning
confidence: 99%